2018
DOI: 10.3171/2018.1.focus17686
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative embolization of skull base meningiomas: current indications, techniques, and pearls for complication avoidance

Abstract: Skull base meningiomas are technically challenging tumors to treat because of their deep vascular supply that can preclude early devascularization during resection. Preoperative embolization of these arterial feeders is thought to decrease blood loss and facilitate resection; however, given the complex and varied anatomy of these skull base lesions, preoperative embolization is not without risk. It is essential for both endovascular and skull base neurosurgeons to understand these risks in light of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(18 citation statements)
references
References 48 publications
(61 reference statements)
1
11
0
1
Order By: Relevance
“…As embolysate technology has evolved over the last decade, several studies have been published on the safety and efficacy of preoperative meningioma embolization, 4,13,16,17,24,25 but none have adequately matched their patients to a nonembolization control group by controlling for detailed tumor-related parameters, which limits the interpretation of previously published findings. In this study, we controlled for important patient-and tumor-related variables between embolization and nonembolization cohorts to assess the effect of preoperative embolization on the surgical outcomes of patients with intracranial meningiomas.…”
mentioning
confidence: 99%
“…As embolysate technology has evolved over the last decade, several studies have been published on the safety and efficacy of preoperative meningioma embolization, 4,13,16,17,24,25 but none have adequately matched their patients to a nonembolization control group by controlling for detailed tumor-related parameters, which limits the interpretation of previously published findings. In this study, we controlled for important patient-and tumor-related variables between embolization and nonembolization cohorts to assess the effect of preoperative embolization on the surgical outcomes of patients with intracranial meningiomas.…”
mentioning
confidence: 99%
“…Embolization of branches of the ICA is considered a risky procedure and can be complicated by embolic accidents such as blindness or ischemic stroke 12–14 . Nevertheless, many authors have reported the possibility of embolization of branches of the ICA for various indications, including skull base tumors 15–19 . However, to our knowledge, there is no report of superselective embolization of branches of the ICA in JNA; the possibility of nonselective embolization under ICA occlusion has been described in one case of JNA 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Studies have analyzed the safety and efficacy of different particulate and liquid embolic agents. Our center prefers PVA particles as the embolic agent, while others advocate Embospheres (trisacryl gelatin),18 liquid embolic agents such as Onyx (ethyl vinyl alcohol copolymer) or nBCA 19–21. Studies have not shown a significant correlation between different embolic agents and degree of angiographic devascularization 11.…”
Section: Discussionmentioning
confidence: 99%